An unusual manifestation in a 19-month-old girl with acute pseudointestinal obstruction and acute flaccid paralysis after a history of hand foot mouth disease - Sanguansermsri, Chinnuwat; Oberdorfer, Peninnah (Biomedical Sciences and Clinical Medicine, 2018)
Background Enterovirus 71 has become the most common cause of acute flaccid paralysis following the global immunization program that help to virtually eradicate poliomyelitis. Most children infected with enterovirus 71 develop herpangina or hand-foot-and-mouth disease (HFM). Some cases are complicated with neurological dysfunctions. Methods The unusual clinical manifestations of a previous healthy 19-month-old girl who presented with HFM followed by signs and symptoms of acute intestinal obstruction.The patient was admitted to the hospital for 48 hours of nasogastric decompression and rectal irrigation. However, within 24 hours after discharge, she developed bilateral leg weakness with absence of reflexes in the lower limbs. Results Cerebrospinal fluid analysis (CSF) was normal on day 6 of disease, but showed high protein levels on day 11. Stool PCR for enterovirus 71 was positive, while CSF PCR for enterovirus 71 was negative. Her MRI scan showed long segmental anterior spinal cord lesions with associated ventral nerve root enhancement. She received methylprednisolone and showed complete recovery at the 6 week after the onset. Conclusions Severe paralytic ileus of the gastrointestinal tract is a sign of an autonomic dysfunction. It can be misdiagnosed as acute gastrointestinal tract obstruction in children with enterovirus 71 infection and may be followed by other neurological complications that need to be monitored. There is also a possibility of a false negative CSF PCR. Combining patient history, physical exams, and additional investigations are needed to help ensure an accurate diagnosis.